THE FACULTY FELLOWSHIP AND ACCOUNTING EDUCATION. - Perry, Kenneth W. (The Accounting Review, 1958)
Abstract The article asserts that accounting teachers have a definite responsibility, not only to accounting students but also to the accounting profession, to keep abreast in this ever-changing accounting world. Although these teachers have certain resources available, at times they may be inadequate and as a consequence they may have to look elsewhere for assistance. When looking elsewhere perhaps the faculty fellowship, if available, will fulfill this need. The faculty fellowship is considered a definite step in the right direction, and it is his hope that other firms will initiate similar programs. In addition to acquiring new, or as the case may be, broadening old technical knowledge the fellowship is also an excellent morale builder or interest stimulator. After teaching for several years and then being exposed to the interest and enthusiasm of the various staff members, it challenges one to want to get back in the classroom and turn out the best product he can possibly produce. Teaching from the textbook from day to day may not be as stimulating as it should be, so perhaps teachers need to be reminded occasionally that they are members of a vital and dynamic profession.